2004
DOI: 10.1097/00004770-200401000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Endodontic Retreatment: A 2-yr Follow-up

Abstract: Retreatment is common in endodontics. The purpose of this article was to classify the different clinical situations encountered in retreatment cases and relate them to the outcome after an observation period of 24 months. A total of 425 patients (452 teeth) from 451 patients, consecutively admitted for root-canal retreatment, were monitored during a 24-month period. All teeth (254 molars, 107 premolars, and 91 single-root anterior teeth) were divided into two major categories: teeth with modified anatomy from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
178
0
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(196 citation statements)
references
References 17 publications
7
178
0
11
Order By: Relevance
“…The literature reports variable success percentages for retreatment ranging from 40%-100% (23); the variability of the outcome in endodontic retreatment is related to different factors: patient age and the types of teeth treated (24), the presence of alterations in the natural course of the root canals (25), the possibility of removing the coronal restorations to access the pulp chamber (2), the techniques used to remove the existing filling materials, and the possibility of repairing pathologic or iatrogenic defects (26). In a recent cohort clinical study (Toronto Study Phase 3-4) of a total of 126 teeth examined at 4 -6 years of follow-up, 104 teeth (83%) were classified as healed.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports variable success percentages for retreatment ranging from 40%-100% (23); the variability of the outcome in endodontic retreatment is related to different factors: patient age and the types of teeth treated (24), the presence of alterations in the natural course of the root canals (25), the possibility of removing the coronal restorations to access the pulp chamber (2), the techniques used to remove the existing filling materials, and the possibility of repairing pathologic or iatrogenic defects (26). In a recent cohort clinical study (Toronto Study Phase 3-4) of a total of 126 teeth examined at 4 -6 years of follow-up, 104 teeth (83%) were classified as healed.…”
Section: Discussionmentioning
confidence: 99%
“…Various adjuvant techniques have been used to overcome the problem. 14 Several studies have shown that oral bacteria are sensitive to photodynamic therapy (PDT). 15,16 In recent years, in vitro [17][18][19][20][21][22][23][24][25][26] and in vivo [27][28][29] studies have been performed to investigate the antibacterial effect of the PDT on the microorganisms in root canal.…”
Section: Introductionmentioning
confidence: 99%
“…This could result in inadequately cleaned canals with the likelihood of persistent apical perioodontitis [29]. Sauaia et al, [30] found that the distal (furcal) root wall of the mesio-buccal canal of a mandibular molar is thinner in teeth with long roots (24 mm) than in short-rooted teeth (19 mm); it can therefore be justifiably assumed that strip perforations might occur more frequently in mandibular teeth with long roots than short-rooted mandibular teeth.…”
Section: Discussionmentioning
confidence: 99%